(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Solar power is one of the fast-growing promising areas of renewable energy use. The article is devoted to the use of solar radiation energy in private households of Ukraine. It is noted that the amount of solar radiation is high enough to create solar power facilities throughout Ukraine. Based on the results of the research, it was found that households that have installed photovoltaic power station are fully self-sufficient in electricity and are the most energy efficient, as the surplus of environmentally clean electricity produced is sold at a "green" tariff. Based on the data of the study of the state of installation of solar power plant in private households, has been made a forecast of the development potential of this electricity sector for the period up to 2024. On the basis of the conducted research, it can be stated that the use of solar power in private households has a sufficiently large perspective to ensure which it is advisable to introduce a net-metering system in Ukraine, which includes the free sale of surplus energy produced on the market with the possibility of "taking" it from this market later.